A previously unreported etiology of trigger toe - (:unkn) unknown (AMER PODIATRIC MED ASSN, 2006)
Trigger toe is a rare entity, with only a few cases reported in the literature. It is usually seen in ballet dancers as a result of compression of the flexor hallucis longus tendon in the tarsal tunnel beneath the medial malleolus. We report a case of trigger toe due to a constricting lesion on the extensor hallucis longus tendon.